IMPLEMENTASI ACCURATE DALAM SISTEM PENCATATAN KAS KECIL DAN HUTANG PADA PERUSAHAAN MANUFAKTUR DI SURABAYA - Paxia Qanita Izzatiy; Siti Sundari (PT. Media Edutama Nusantara, 2026)
The development of information technology has encouraged companies to shift from manual financial recording systems to digital-based accounting systems. This study aims to describe the implementation of Accurate software in recording petty cash and accounts payable at a manufacturing company located in Surabaya. The research employs a descriptive qualitative method with a case study approach. The findings indicate that prior to the implementation of Accurate, the recording of petty cash and accounts payable was still conducted using Microsoft Excel and had not been carried out optimally, which potentially led to recording errors and required a relatively longer processing time. Following the adoption of Accurate, the recording process became more structured and efficient, as transactions are processed automatically, journal entries are generated directly, and financial information is presented in real time. The implementation of Accurate has been proven to enhance the effectiveness and reliability of the company’s financial recording system.